Association of Parenting Practices, Nutritional Intake,and Economic Status with Stunting Among Children Aged 24–59 Months - Umratul Fatiha; Nur Husnul Khatimah; Muammar Iksan; Dea Zara Avila (Universitas Muhammadiyah Palembang, 2026)
Stunting is a chronic nutritional problem among toddlers, characterized by impaired height-for-age growth. The occurrence of stunting can be influenced by various factors, including the quality of care, adequate nutritional intake, and the family’s socioeconomic status. This study aims to determine the relationship between parenting practices, nutritional intake, and socioeconomic status with the prevalence of stunting among children aged 24–59 months in the service area of the Penanae Community Health Center, Bima City. This study employed a quantitative approach with an analytical observational design and a cross-sectional method. The sample consisted of 78 toddlers selected using simple random sampling, comprising 39 toddlers in the stunting group and 39 toddlers in the non-stunting group. Data were collected through interviews using a questionnaire on parenting practices and socioeconomic status, nutritional intake measurements using the Food Frequency Questionnaire (FFQ), and height measurements based on the height-for-age (H/A) indicator. Data analysis was performed using the chi-square test and logistic regression. The results showed an association between parenting practices (p<0.001), nutritional intake (p=0.002), and socioeconomic status (p=0.042) and the incidence of stunting. Multivariate analysis showed that parenting practices were the most influential factor on the incidence of stunting, with an OR of 6.318 (95% CI: 2.104–18.973; p=0.001) Based on the research findings, improving the quality of child-rearing practices, meeting nutritional needs, and providing support for families’ economic conditions should be considered as measures to prevent stunting in toddlers.